The chiropractic college admission test: a proposal for its development and use - Violato, Claudio (1996)
A cardinal characteristic of any profession is self-regulation. It is argued in the present paper that chiropractic has now reached a level of professional maturity that indicates the need for the final aspect of self-regulation: a standardized selection approach into professional schools or colleges. Quality control of membership can then begin at the entry point into the profession. An admission test - the Chiropractic College Admission Test (CCAT) - is proposed and outlined for use for the selection of candidates into chiropractic colleges. Such a test would be beneficial for students applying to the colleges, regulatory and licensing boards, to the profession as a whole, to the chiropractic colleges, to other professions, and to government as well as the general public. The proposed CCAT contains elements that are general to many health professions such as knowledge of the biological and physical sciences, verbal and linguistic reasoning and visual perceptual ability. The test, however, is proposed to have elements that are unique to chiropractic. Based on the performance of other admission tests (e.g. Dental Admission Test, Medical College Admission Test), it is argued that the CCAT could be constructed and used to have the highest technical properties of validity and reliability. Such a test would become an integral tool in maintaining quality assurance, beginning at the earliest point of the profession.